2019
DOI: 10.1097/ico.0000000000002151
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lubricin in the Human Amniotic Membrane

Abstract: Purpose-Lubricin, a boundary lubricant, is the body's unique anti-adhesive, anti-fibrotic, antifriction and anti-inflammatory glycoprotein. This amphiphile is produced by numerous tissues and acts to regulate a number of processes, such as homeostasis, shear stress, tissue development, innate immunity, inflammation and wound healing. We hypothesize that lubricin is also synthesized and expressed by the amniotic membrane (AM), which also possesses anti-adhesive, anti-fibrotic and anti-inflammatory properties. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Authors have also shown the glycoprotein Lubricin to be present in AM, which is a naturally occurring boundary lubricant with anti-inflammatory, anti-adhesive, and anti-friction properties and this is likely to play a role in the wide-ranging functions of AMT. 40 Fibrosis development is driven by the formation of myofibroblasts, which form following the activation of keratocytes, as a response to the disruption of the ocular surface. The anti-fibrotic features of amniotic membrane act in a complementary fashion to the anti-inflammatory nature of the tissue.…”
Section: The Wide-ranging Properties Of Amniotic Membrane General Strmentioning
confidence: 99%
“…Authors have also shown the glycoprotein Lubricin to be present in AM, which is a naturally occurring boundary lubricant with anti-inflammatory, anti-adhesive, and anti-friction properties and this is likely to play a role in the wide-ranging functions of AMT. 40 Fibrosis development is driven by the formation of myofibroblasts, which form following the activation of keratocytes, as a response to the disruption of the ocular surface. The anti-fibrotic features of amniotic membrane act in a complementary fashion to the anti-inflammatory nature of the tissue.…”
Section: The Wide-ranging Properties Of Amniotic Membrane General Strmentioning
confidence: 99%
“…Microbial mutation breeding methods have been widely used in the fermentation industry, including physical mutation methods, such as ultraviolet radiation and ion beam , and chemical mutagenesis methods, such as sodium azide, diethyl sulfate, and ethylmethane sulfonate . However, there had been few reports on the role of ARTP in improvement of enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed data from 223 AMT cases in 191 patients with NHCUs of different etiologies. In all cases, cryopreserved AMs were used as they contain high concentrations of growth factors [ 7 , 44 ] and lubricin, a boundary lubricant ( Figure 1 ) [ 17 , 45 ]. Cryopreserved AMs are most widely used because of their biosafety [ 43 ] The protocols of provincial and regional biobanks established by the National Health System were followed, with sterility controls and serological studies of donors and recipients [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…This tissue has multiple biological properties, including the induction of cell proliferation, reduction of neovascularization, anti-scarring properties, increasing migration of cells such as keratinocytes, pool corneal regeneration, and little or no immunogenicity [ 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Heavy chain hyaluronan/pentraxin 3 (HC-HA/PTX3), a matrix component of AM, is a key factor responsible for the aforementioned AM’s properties [ 16 , 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation